1996
DOI: 10.1128/aem.62.2.323-327.1996
|View full text |Cite
|
Sign up to set email alerts
|

Physiochemical characterization of the nisin-membrane interaction with liposomes derived from Listeria monocytogenes

Abstract: Mechanistic information about the bacteriocin nisin was obtained by examining the efflux of 5(6)-carboxyfluorescein from Listeria monocytogenes-derived liposomes. The initial leakage rate (percentage of efflux per minute) of the entrapped dye was dependent on both nisin and lipid concentrations. At all nisin concentrations tested, 5(6)-carboxyfluorescein efflux plateaued before all of the 5(6)-carboxyfluorescein was released (suggesting that pore formation was transient), but efflux resumed when more nisin was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 31 publications
5
45
0
1
Order By: Relevance
“…However, at high concentration of nisin (1000 IU ml −1 ), the bacteriocin induces both K ¦ leakage and cell death as described for Gram-positive bacteria (Abee et al 1994). These results show that K ¦ leakage and bactericidal activity of nisin depend both on the bacteriocin concentration and on the cell density as reported by Winkowski et al (1996) and Ogden (1986). These authors showed that an increase of nisin concentration led both to an increase of cytoplasmic compounds leakage and to an increase of killed cells.…”
Section: Discussionsupporting
confidence: 76%
“…However, at high concentration of nisin (1000 IU ml −1 ), the bacteriocin induces both K ¦ leakage and cell death as described for Gram-positive bacteria (Abee et al 1994). These results show that K ¦ leakage and bactericidal activity of nisin depend both on the bacteriocin concentration and on the cell density as reported by Winkowski et al (1996) and Ogden (1986). These authors showed that an increase of nisin concentration led both to an increase of cytoplasmic compounds leakage and to an increase of killed cells.…”
Section: Discussionsupporting
confidence: 76%
“…The mode of action of nisin is believed to be disruption of membrane function induced by pore formation in the bacterial membrane (Moll et al 1996) and subsequent leakage of cellular material. This has been demonstrated in vitro by Winkowski et al (1996).…”
Section: Introductionmentioning
confidence: 73%
“…Heat Nisin Heat + nisin ---------------------------------------------------- -------------------------------------------------- in the membrane (Winkowski et al 1996). Flow cytometry proved that a single application of heat has little effect, and low nisin concentrations only moderate effects, on membrane permeability.…”
Section: ------------------------------------------------------Regionsmentioning
confidence: 99%
“…When acting individually, the effect of nisin (Mansour et al 1998) and monolaurin was enhanced as pH value and spore load decreased. The enhanced activity of nisin (Oscroft et al 1990;Hurst and Hoover 1993;Kumar and Prasad 1994; Roberts and Hoover 1996) and monolaurin Marshall 1992, 1996;Kabara 1993;Stillmunkes et al 1993) at low pH values could be attributed to their greater solubility at acidic pH (Hurst and Hoover 1993;Kabara 1993;Ferreira and Lund 1996) or to the increased susceptibility of micro-organisms when hostile environmental conditions (low pH) were associated with inhibitors (Wang and Johnson 1992;Winkowsky et al 1996). Germination and growth of B. licheniformis at acidic pH (between 5·0 and 5·6) occurred but was delayed compared with pH values between 6·0 and 7·0 (data not centre of the domain Fig.…”
Section: Discussionmentioning
confidence: 99%